2003
DOI: 10.1097/01.ccm.0000094260.05266.f4
|View full text |Cite
|
Sign up to set email alerts
|

High-dose vasopressin is not superior to norepinephrine in septic shock*

Abstract: Vasopressin, in doses sufficient to replace the vasopressor norepinephrine, had mixed effects in septic shock patients. Hepatosplanchnic blood flow was preserved during substantial reduction in cardiac output. An increased gastric PCO2 gap suggests that the gut blood flow could have been redistributed to the disadvantage of the mucosa. Based on these limited data, it does not appear beneficial to directly replace norepinephrine with vasopressin in septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
2
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(120 citation statements)
references
References 24 publications
6
105
2
7
Order By: Relevance
“…In a randomized controlled open-label trial in patients with septic shock, additional use of AVP disclosed no changes in pCO 2 g-a and a higher creatinine clearance in comparison to NE alone [50]. This was in contrast to other reports of patients with septic shock; both additional continuous infusion of low dose AVP as well as replacement of NE by high dose AVP resulted in a significant increase of pCO 2 g-a [51,52]. Equally conflicting data in animal studies are suggested to be related to volume status and cardiac performance [53].…”
Section: Vasopressorscontrasting
confidence: 54%
“…In a randomized controlled open-label trial in patients with septic shock, additional use of AVP disclosed no changes in pCO 2 g-a and a higher creatinine clearance in comparison to NE alone [50]. This was in contrast to other reports of patients with septic shock; both additional continuous infusion of low dose AVP as well as replacement of NE by high dose AVP resulted in a significant increase of pCO 2 g-a [51,52]. Equally conflicting data in animal studies are suggested to be related to volume status and cardiac performance [53].…”
Section: Vasopressorscontrasting
confidence: 54%
“…This indicates that although there were no significant outcome differences, the blood pressure effects of AVP were not equivalent to NE at the doses used in the protocol. This finding is consistent with previous studies, which found that AVP doses of 0.15-0.47 units/min were needed to replace NE as the sole vasoactive agent in patients with septic shock (13,14). Despite promising retrospective data (15,16), monotherapy or early initiation of AVP at doses up to 0.06 units/min appears unlikely to be sufficient to achieve a goal blood pressure in patients with septic shock and adjunctive vasoactive therapy will be needed, which may mask the potential renal benefits of AVP.…”
supporting
confidence: 83%
“…[125][126][127] Current treatment doses of 0.01-0.04 units/min are meant to reflect physiologic replacement doses. High doses of 0.06-1.8 units/min (as traditionally used) 128,129 are not recommended in the context of septic shock because of reported adverse events. 130,131 Epinephrine (1-10 µg/min) may be considered for patients unresponsive to other vasopressors.…”
Section: Vasoactive Agentsmentioning
confidence: 99%